Evaluation of sporting success in Austria. An institutional economics analysis - Barth, M.; Emrich, E.; Daumann, F. (Diskussionspapiere des Europäischen Instituts für Sozioökonomie e. V., 20, 2017)
In analysis of Austrian elite sport, a distinction can be made between hierarchical and market organization. Following Williamson, the question of a superiority of governance form caused by the factor specificity of investments is being investi-gated. The results from an applied logit-loglinear model on data from survey with Austrian `squad-athletes` show that apparently there exists no such superiority. Further investigation of data shows that these results appear to be caused by Aus-tria`s "pre-conditions". In a hybrid form of organization like in Austria centraliza-tion might have exceeded the optimal extend and congruency of different products seem to be overemphasized.